Insights into antimicrobial agent sulfacetamide transformation during chlorination disinfection process in aquaculture water. Issue 24 (20th April 2021) - Guo, Yaoguang; Liu, Zhiyuan; Lou, Xiaoyi; Fang, Changling; Wang, Pu; Wu, Genying; Guan, Jie
Abstract : A systematic study for degradation kinetics and transformation mechanism of sulfacetamide antibiotic, and the potential formation of H-DBPs represented by HAAs in the chlorination process is explored. Abstract : Antibiotic addition and chlorination are two common processes in fishery culture. Antibiotic residues not only pollute aquaculture water, but are also one of the potential precursors of disinfection by-products (DBPs) during chlorination. The degradation kinetics, products identification and reaction mechanism of sulfacetamide (SFA), a new sulfonamides antibiotics, and potential formation of haloacetic acids (HAAs) in chlorination were explored. The results showed that the degradation of SFA followed pseudo first-order kinetic model, and chlorinating agent dose, pH of water, water temperature, NH4 +, HCO3 − and humic acid (HA) had various effects on the degradation of SFA and the yields of HAAs. The presence of Br − accelerated both the degradation rate of SFA and more formation of Br-DBPs. Through the identification of intermediate products, we proposed the transformation pathway of SFA during the chlorination disinfection process. Namely, in this NaClO disinfection system, the C–S bond between the sulfonyl group and benzene ring, and S–N bond between sulfonyl and acylamino of SFA were broken, and then the primary formed groups were further oxidized to produce intermediates, such as chloroanilines and chlorophenols. And then chlorophenols were subsequently chlorinated to form toxic HAAs. The present study might be of significance for the evaluation of effective degradation of SFA and potential production of halogenate-DBPs (H-DBPs) during the chlorination disinfection process in aquaculture water.